Optimization of Î²-Cyclodextrin Production from Sago Starch using Recombinant Cyclodextrin Glycocyltransferase from Bacillus sp. A2-5a (Microbiology Indonesia, 2014)
Cyclodextrin (CD) is a cyclic oligosaccharide molecule which is classified into three types: Î±-CD, Î²-CD, and Î³-CD, each consists of 6, 7, and 8 glucose units. CDs are produced enzymatically using starch as the substrate catalyzed by CD glycosyltransferase (CGTase). This research was aimed to determine optimum condition of Î²-CD production from sago starch using recombinant CGTase (rCGTase) from Bacillus sp. A2-5a, and using the optimum condition, Î²-CD production was done at 100 mL scale using complexing agents. In this study, rCGTase was overproduced in Escherichia coli BL21(DE3) and purified applying Ni-NTA affinity chromatography with gradual elution of imidazole and concentrated using Nanosep column. The purified rCGTase was 76.39 kDa in size and displayed Î²-cyclization and hydrolysis activities using zymography. The results showed that optimum conditions for Î²-CD production was achieved when preheated sago starch of 0.5% (w/v), enzyme of 2.6x10-2 U, and N,N-dimethylformamide (DMF) as complexing agent of 1% (v/v) were used and the reaction time was 8 h. When DMF of 1% (v/v) was added repeatedly at 100 mL scale production, the highest concentration of Î²-CD was obtained at the reaction time of 8 h. This research reported for the first time the optimum condition of b-CD production at 100 mL scale using rCGTase from Bacillus sp. A2-5a with DMF as complexing agent.